A Study on the Effects of Loading Axial Pressure Rate on Coal Mechanical Properties and Energy Evolution Law. (24th September 2022) - Guo, Hongjun; Sun, Zhongguang; Ji, Ming; Liu, Dapeng; Nian, Lihui; Wu, Yongfeng
Abstract : Due to the unique nature of the coal mining industry, safety is always one highly upheld premise of high production and high efficiency. According to the stress adjustment characteristics of the surrounding rocks in roadway excavation under a nondisruptive environment, the stress paths of unloading confining pressure and loading axial pressure were designed creatively and vividly, and the coal mechanical properties and energy evolution law under different loading axial pressure rates were studied through a series of experiments. As the loading axial pressure rate increases, the mechanical parameters at the time of coal failure show a nonlinear increase in the peak strength, the confining pressure, and the axial strain, while the variation laws of lateral strain and volumetric strain are not obvious. In addition, the failure mode transfers from the brittle failure to the ductile failure. In terms of energy, the positive work done by the axial pressure, the total work, and the elastic strain energy tend to increase nonlinearly, while the negative work done by the confining pressure and the plastic strain energy increase conversely. The elastic strain energy conversion rate increases logarithmically, indicating that a higher loading axial pressure rate tends to increase the probability and strength of coal instantaneous failure and subsequent dynamic behaviors. The research results reveal that providing an appropriate pressure relief and timely support after the roadway excavation in the actual production process can effectively reduce the energy level of the environment at the location of the surrounding rock support system, which is conducive to the roadway support and the surrounding rock stability control. Furtherly, it has important reference value for the roadway excavation and other underground engineering excavation and support operations and is of great significance to promote the development of deep resources.